2016
DOI: 10.1111/jace.14404
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Preparation to Promote the Adsorption of Mg‐Al Layered Double Hydroxide

Abstract: This study presents an interesting phenomenon of the simultaneous occurrence of adsorption and synthesis of Mg–Al layered double hydroxide (Mg–Al–LDH) by stirring a precursor in an aqueous solution with methyl orange (MO) as target adsorbate with the precursor prepared by first milling Mg(OH)2 for 1 h followed by another 3 h milling with Al(OH)3.The prepared precursor and LDH samples were characterized by a set of analytical methods including X‐ray diffraction (XRD), thermogravimetry/differential scanning calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
(51 reference statements)
3
7
0
Order By: Relevance
“…The excellent adsorption performances of the Mg-Al LDH precursor 18 and ettringite precursor 19 were reported in our previous papers. In this work, the precursor of Zn-Al LDH also shows outstanding adsorption efficiency toward MO.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…The excellent adsorption performances of the Mg-Al LDH precursor 18 and ettringite precursor 19 were reported in our previous papers. In this work, the precursor of Zn-Al LDH also shows outstanding adsorption efficiency toward MO.…”
Section: Resultssupporting
confidence: 69%
“…The mechanism of enhanced adsorption. The enhanced adsorption performance of the Mg-Al-OH LDH precursor toward MO was reported in our previous paper, 18 in which no MO intercalation reaction was observed because the OH À anion of the precursor of Mg-Al-OH LDH could not exchange with the MO molecule. Thus, it could be concluded that the enhanced adsorption performance of the Mg-Al-OH LDH precursor toward MO is a result of the disorderly state of the precursor, which could provide more adsorption sites than the closed structure of the LDH.…”
Section: 21supporting
confidence: 58%
See 2 more Smart Citations
“…Second wet milling step was replaced by agitation to increase the crystallinity. The mixture of Mg(OH) 2 and Al(OH) 3 was milled for 1 h using planetary ball mill; then, the mixture was agitated in water for 1-5 h at room temperature [149]. The XRD result showed the increased crystallinity of LDH observed by the increasing of the sharpness of the diffraction peak when prolonging the agitation time.…”
Section: Mechanochemical Synthesesmentioning
confidence: 99%